Random SU(2) invariant tensors. (29th March 2018) - Li, Youning; Han, Muxin; Ruan, Dong; Zeng, Bei
Abstract: SU(2) invariant tensors are states in the (local) SU(2) tensor product representation but invariant under the global group action. They are of importance in the study of loop quantum gravity. A random tensor is an ensemble of tensor states. An average over the ensemble is carried out when computing any physical quantities. The random tensor exhibits a phenomenon known as 'concentration of measure', which states that for any bipartition the average value of entanglement entropy of its reduced density matrix is asymptotically the maximal possible as the local dimensions go to infinity. We show that this phenomenon is also true when the average is over the SU(2) invariant subspace instead of the entire space for rank- n tensors in general. It is shown in our earlier work Li et al (2017 New J. Phys .19 063029) that the subleading correction of the entanglement entropy has a mild logarithmic divergence when n   =  4. In this paper, we show that for n   >  4 the subleading correction is not divergent but a finite number. In some special situation, the number could be even smaller than 1/2, which is the subleading correction of random state over the entire Hilbert space of tensors.